Healthcare utilization after stroke in Canada- a population based study - Adebimpe O. Obembe; Lisa A. Simpson; Brodie M. Sakakibara; Janice J. Eng (BMC, 2019)
Abstract Background More people are surviving stroke but are living with functional limitations that pose increasing demands on their families and the healthcare system. The aim of this study was to determine the extent to which stroke survivors use healthcare services on a population level compared to people without a stroke. Methods This was a cross-sectional population-based survey that collected information related to health status, healthcare utilization and health determinants using the 2014 Canadian Community Health Survey. Healthcare utilization was assessed by a computer-assisted personal interview asking about visits to healthcare professionals in the last 12 months. Negative binomial regression was used to estimate the incidence rate ratios (IRR) and 95% confidence intervals (CI) for the number of health professional visits between stroke survivors and people without a stroke. The regression models were adjusted for demographics, as well as for mobility, mood/anxiety disorder and cardiometabolic comorbid conditions. Results The study sample included 35,759 respondents (948 stroke, 34,811 non-stroke) and equate to 12,396,641 (286,783 stroke; 12,109,858 non-stroke) when sampling weights were applied. Stroke survivors visited their family doctor the most, and stroke was significantly associated with more visits to most healthcare professionals [e.g., family doctor IRR 1.6 (CI 1.4-1.8); nurse IRR 3.0 (CI 1.8-4.8); physiotherapist IRR 1.8 (CI 1.1-1.9); psychologist IRR 4.0 (CI 1.1-5.7)] except the dental practitioner, which was less [IRR 0.7 (CI 0.6-0.9)]. Mood/anxiety condition, but not cardiometabolic comorbid condition increased the probability of visiting a family doctor or social worker/ counsellor among people with stroke. Conclusion Stroke survivors visited healthcare professionals more often than people without stroke, and were approximately twice as likely to visit with those who manage problems that may arise after a stroke (e.g., family doctor, nurse, psychologist, physiotherapist). The effects of a stroke include mobility impairment and mood/ anxiety disorders. Therefore, adequate access to stroke-related healthcare services should be provided for stroke survivors, as this may improve functional outcome and reduce future healthcare costs.